The impact of the communication system on some organizational adjustment options Aimed at addressing the digital divide Analysis of opinions of managers in Iraqi mobile phone companies - علي عبد الستار محمد; محمد اثمار عبد الرزاق; محمد رضاء حازم (Journal of Economics and Administrative Sciences, 2012)
This research began by explaining its variables and dimensions especially the digital gap, which the authors explained it elaborately beginning with the concept, the reasons blind its emergence of its measurement, and how to treat it. The authors supposed the potentiality of relying on enforcing knowledge in general and the groups suffer from this gap in particular, especially the targeted knowledge to treat its subject. As enforcing knowledge usually depends on some strategies or choices of organizational orientation among them is learning and training from one side, and communication, as an indicating factor for organizational effectiveness as the authors refer from the other side. So authors tried to deal with the two mentioned choices in away effected by communication and then transform this effect as well as to other special effects to the targeted knowledge to treat the digital gap. The authors through their achievement to the set of their data analysis which the obtained concluded that their supposition is true. In the light of their conclusion they presented their suggestions that their is an ability to execute their point of view to help the organizations in our country to treat their digital gap as a step toward treating the gap our country suffers from such that make it one of the prominent countries as far as the problems of digital gap as Malaysia and its growth.